Genetic deletion of IL‐6 increases CK‐MB, a classic cardiac damage marker, and decreases UPRmt genes after exhaustive exercise. (12th April 2022) - Rovina, Rafael L.; Pinto, Ana P.; Muñoz, Vitor R.; da Rocha, Alisson L.; Rebelo, Macario A.; Teixeira, Giovana R.; Tavares, Maria Eduarda A.; Pauli, José R.; de Moura, Leandro P.; Cintra, Dennys E.; Ropelle, Eduardo R.; da Silva, Adelino S. R.
Abstract: The intensity, duration, type of contraction, and muscle damage influence interleukin‐6 (IL‐6) response to acute exercise. However, in response to an exhaustive exercise session, the upregulation of IL‐6 in the serum and heart is associated with an inflammatory condition and can inhibit autophagy. This study aimed to investigate the role of IL‐6 in autophagy pathway responses and mitochondrial function in the heart of mice submitted to acute exhaustive physical exercise. The mice were allocated into three groups, five animals per group, for the wild type (WT) and the IL‐6 knockout (IL‐6 KO): Basal (sedentary; Basal), 1 h (after 1 h of the acute exercise; 1 h), and 3 h (after 3 h of the acute exercise; 3 h). After the specific time for each group, the blood was collected, each mouse heart was removed, and the left ventricle (LV) was isolated. In summary, under basal conditions, without the influence of the acute exercise, the IL‐6 KO group showed lower number of nuclei in the cardiac tissue, but higher collagen deposition; lower messenger RNA (mRNA) levels of Prkaa1 and Mtco 1, but higher mRNA levels of Ulk1 ; and higher protein levels of the ratio p‐AMPK/AMPK in the heart when compared to WT at the same time point. After the acute exercise (1 and 3 h), the IL‐6 KO group had lower mRNA levels of Tfam, Mtnd1, Mtco1, and Nampt in the heart when compared to WT after exercise; higher serum levels of creatine kinase (CK), CK‐MB, and lactate dehydrogenase for the IL‐6 group when compared to the WT group after the exercise. Specifically, the heat‐shock protein 60 protein levels in the heart increased 3 h after exhaustive exercise in the WT group, but not in the IL‐6 KO group. The study emphasizes that IL‐6 may offer cardioprotective effects, including mitochondrial adaptations in response to acute exhaustive exercise. Significance statement: The characterization of cytokines, like interleukin‐6 (IL‐6), which has pro‐ and anti‐inflammatory effects in the physiological and cardiac responses to physical exercise, is necessary for the context of metabolic health. In response to physical exercise, IL‐6 can promote anti‐inflammatory effects; however, after an exhaustive exercise session, the upregulation of IL‐6 in the serum is related to a pro‐inflammatory state. This study demonstrated that IL‐6 might exert cardioprotective effects and mitochondrial adaptations in response to acute exhaustive exercise.